Ethnography: use, potentialities and limits in health research - Andrea Caprara; Lucyla Paes Landim; Philip Sidney Pacheco Badiz (Faculdade de Medicina de Botucatu (Unesp), 2008)
Ethnography is used more and more often to study different subjects in health domain: the functioning and evaluation of healthcare systems; epidemiological research; laboratorial scientific research; biotechnology research; genetic research, among others. Certain methodological questions arise from critical reading of these works: How has ethnographic research evolved over the last few decades? What elements characterize ethnographic research as applied to healthcare? This paper seeks to reflect on these questions through two successive developments: 1. the evolution of the ethnographic method and its use in research on health; 2. the methodological aspects of an ethnographic study conducted with elderly people in the city of Fortaleza, focusing on participant observation.